Pengaruh PDRB, Upah Minimum dan Jumlah Penduduk terhadap Tingkat Partisipasi Angkatan Kerja Pada Kabupaten/Kota di Jawa Barat Tahun 2007 - 2014 - Rindi Septian Prenggondani (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aimed to analyze the influence of the GRDP, Minimum Wages and Population on the Labour Force Participation Rate on District / City in West Java year 2007 - 2014. This study uses a quantitative approach. The data used in this research is secondary data in the form of panel data. Methods of data collection in this research is to find and merge secondary data from BPS data in  2007 - 2014. The dependent variable in this study is the Labor Force Participation Rate (LFPR), while Independent variables used is Gross Regional Domestic Product (GRDP), wages minimum and population. The results showed the GRDP and Population variables have a significant influence in a positive direction towards LFPR.Keywords: Labor Force Participation Rate (LFPR), Gross Regional Domestic Product (GRDP), Minimum Wages and Population